Effect of high-k FinFET performance / Fatin Syamila Mohammad - Mohammad, Fatin Syamila (2013)
Scaling down transistor to 45nm node and below might require new processing steps such as new gate stack or new device structure such as FinFET. Thus, in this work the use of high-k gate insulator - hafnium oxide (Hf02) on FinFET performance was investigated. SPICE model was used to describe the real device operation and designing a practical analog circuit for the AC analysis. Therefore, only the gate insulator is changed in the SPICE model from silicon oxide, SiO2 to HfO2 and the difference of the turn on current (ION) is compared between planar and FinFET SiO2 gate insulator with HfO2 gate insulator FinFET transistor. The simulation results for 22nm node on inverter and chain inverter application show that better performance was obtained for FinFET compared to planar bulk CMOS.